Cytological features of warthin‐like papillary thyroid carcinoma: A case report with review of previous cytology cases. Issue 9 (27th April 2017) - Vallonthaiel, Archana George; Agarwal, Shipra; Jain, Deepali; Yadav, Rajni; Damle, Nishikant A.
Abstract: Warthin‐like papillary thyroid carcinoma (WLPTC) is a rare morphological variant of papillary thyroid carcinoma which mimics various benign and malignant lesions on thyroid aspiration cytology. As correct cytological diagnosis is the cornerstone for appropriate patient management, awareness of the salient cytomorphological characteristics of this tumor is essential. Here, we present cytological features of a case of WLPTC along with discussion of the common differential diagnoses and a brief review of the literature to ascertain the most consistent cytological findings of WLPTC. The present case also harboured BRAFV600E mutation which is the commonest molecular alteration seen in WLPTC.